Effect of a Drug-Eluting Stent vs. Bare Metal Stent for the Treatment of Symptomatic Intracranial and Vertebral Artery Stenosis - Si, Jiang-Hua; Ma, Ning; Gao, Feng; Mo, Da-Peng; Luo, Gang; Miao, Zhong-Rong (Frontiers in Neurology, 2022)
Background For patients with symptomatic intracranial and vertebral artery stenosis who receive endovascular treatment, in-stent restenosis (ISR) is associated with the recurrence of ischemic stroke. This study evaluated a drug-eluting stent (DES) vs. bare metal stent (BMS) for the treatment of symptomatic intracranial and vertebral artery stenosis. Methods The trial was a multicenter, 1:1 randomized, prospective feasibility clinical trial with 10 participating centers in China from March 2014 to October 2015. Eligible patients had symptomatic intracranial and vertebral artery stenosis (70%−99%) and had medical drug treatment failure. The primary endpoint was the rate of in-stent restenosis at 180 days of randomization. The secondary endpoint was a composite of the following two outcomes: (1) ischemic stroke or transient cerebral ischemia (TIA) in the same territory as the presenting event (distal to the target lesion) between 30 days and 1 year after randomization and (2) successful stent implantation. The safety outcome was the presence of stroke in any territory and death within 30 days of randomization or adverse events. Group t-tests or Wilcoxon rank-sum tests were used for the intergroup comparison of quantitative data according to the data distribution. The chi-square test or exact probability method was used for the classification data. The Wilcoxon rank-sum test or CMH test was used for the categorical data. Results We enrolled 188 patients at 10 medical centers in China (92 assigned to the DES group and 96 to the BMS group). The mean age of the 188 study participants was 61.6 years (range, 38–75 years); 152 participants (80.9%) were male. There were 28 patients (43.8%) with an ISR at 180 days in the BMS group and 10 patients (14.5%) in the DES group [risk difference, 29.3% (95% CI, 14.5%−44.0%); P = 0.001]. The percent of patients with ischemic stroke or TIA in the same territory between 30 days and 1 year was 5.2% (5/96) in the BMS group and 2.2% (2/92) in the DES group [risk difference, 3.0%; (95% CI, −2.3% to 8.2%); P = 0.354]. The percent of patients with successful stent implantation was 99.0% (95/96) in the BMS group and 97.8% (90/92) in the DES group [risk difference, 1.1%; (95% CI, −1.7% to 3.9%); P = 0.584]. In total, five patients (5.2%) in the BMS group and three patients (3.3%) in the DES group [risk difference, 1.9%; (95% CI, −2.3% to 6.1%); P = 0.721] had stroke in any territory and death within the 30-day follow-up. Total adverse events occurred 167 times in 72 patients (75.0%) in the BMS group compared with 114 times in 59 patients (64.1%) in the DES group [risk difference, 10.9%; (95% CI, −0.1% to 21.7%); P = 0.115]. Conclusions Among patients with symptomatic intracranial arterial stenosis and vertebral artery stenosis, the use of a drug-eluting stent compared with a bare metal stent resulted in a decreased risk of ISR, similar successful stent implantation, and similar adverse events. These findings support the use of a drug-eluting stent for patients with symptomatic intracranial arterial stenosis and vertebral artery stenosis. Clinical Trial Registration http://www.chictr.org.cn/showproj.aspx?proj=148272, identifier: ChiCTR2200055925.